Inhibitive effect of chloroquine towards corrosion of mild steel in hydrochloric acid solution - Singh A.K.; Khan S.; Singh A.; Quraishi S.M.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Corrosion inhibition of mild steel (MS) by chloroquine (CQ) in 1 M HCl was investigated using weight loss, polarization, electrochemical impedance spectroscopy (EIS) and quantum chemical techniques. The inhibitor showed 99 % inhibition efficiency at concentration of 3.1 × 10-4 M. Polarization studies showed that CQ is a mixed-type inhibitor. Adsorption of inhibitor molecules on the MS surface showed Langmuir adsorption isotherm. Thermodynamic parameters led to the conclusion that adsorption is predominantly chemisorption. Quantum chemical calculations were carried out to investigate the corrosion-inhibiting property of CQ. Various parameters such as energy of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), softness of molecule, Mullikan charges on various atoms and number of electrons transferred from inhibitor molecule to metal were calculated and correlated with the inhibiting property of CQ. © 2012 Springer Science+Business Media B.V.